Heavy metal toxicity in agricultural soil due to rapid industrialization in Bangladesh: a review - Proshad, Ram; Kormoker, Tapos; Mursheed, Niaj; Monirul Islam, Md.; Bhuyan, Md. Isfatuzzaman; Sazedul Islam, Md.; Mithu, Tanvir Nahid (International Journal of Advanced Geosciences, 2018)
Heavy metal is a member of loosely defined subset of elements that exhibit metallic properties. It mainly includes the transition metals, some metalloids, lanthanides, and actinides. Heavy metals are ubiquitous in the environment, as a result of both natural and anthropogenic activities. They are stable and cannot be destroyed, and therefore tend to accumulate in the environment. In recent years, there has been a substantial concern over the extent of contamination of the environment with toxic elements. Soil pollution caused by rapid industrial activities has become a worrisome phenomenon due to its impact on soil and environment. Heavy metal pollution in soil arising from industrial discharges significantly poses a great threat to the environment. Heavy metals come to the soil by several ways and the soil becomes toxic which cause serious problem to the environment. In toxic soil, microorganisms cannot persist and there create an imbalance situation in the soil. The main objective of this study was to assess the problem of heavy metal contamination in industrial area soil in Bangladesh with environmental risk assessment.